2014
DOI: 10.1186/1477-5956-12-10
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic sample preparation for blast wound characterization

Abstract: BackgroundBlast wounds often involve diverse tissue types and require substantial time and treatment for appropriate healing. Some of these subsequent wounds become colonized with bacteria requiring a better understanding of how the host responds to these bacteria and what proteomic factors contribute wound healing outcome. In addition, using reliable and effective proteomic sample preparation procedures can lead to novel biomarkers for improved diagnosis and therapy.ResultsTo address this need, suitable sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Vacuum, drainage, or other external devices were used in 124 of the 280 (44%) studies and thus were the most frequently used methods of sample collection 22–27,29–146 ; the vast majority of sample collections using this method (75%, 103/138), were from surgical wounds (Figure 2B). Three other frequently used methods were extraction from absorbent material (31%, 86/280),…”
Section: Resultsmentioning
confidence: 99%
“…Vacuum, drainage, or other external devices were used in 124 of the 280 (44%) studies and thus were the most frequently used methods of sample collection 22–27,29–146 ; the vast majority of sample collections using this method (75%, 103/138), were from surgical wounds (Figure 2B). Three other frequently used methods were extraction from absorbent material (31%, 86/280),…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, 14-high-abundant proteins from human biological fluids were greatly decreased by MARS Hu-14, which improved the resolution and dynamic range for proteomic analyses. This technology has been applied successfully for investigations of low abundance members of plasma/serum proteomes and has led to the discovery of biomarkers (Silbiger et al, 2011;Chromy et al, 2014;Johansen et al, 2009;Darde et al, 2007). The present data showed that some lower abundance protein bands were enriched after removing higher abundance proteins.…”
Section: Discussionmentioning
confidence: 61%
“…All effluent samples were subjected to removal of high abundant proteins to improve overall spot clarity and separated by 2-D DIGE according to protocols established by Chromy et al [ 16 ]. Spot maps were analyzed by DeCyder 7.0 by which a total of 1800 spots were detected and quantified in each the 22 gels using the DIA module, and gel-to-gel spot matching was performed using the BVA module.…”
Section: Resultsmentioning
confidence: 99%